Apple in China : the capture of the world's greatest company - McGee, Patrick (Reporter) (Scribner, 2025)
"After struggling to build its products on three continents, Apple was lured by China's seemingly inexhaustible supply of cheap labor. Soon it was sending thousands of engineers across the Pacific, training millions of workers, and spending hundreds of billions of dollars to create the world's most sophisticated supply chain. These capabilities enabled Apple to build the 21st century's most iconic products--in staggering volume and for enormous profit. Without explicitly intending to, Apple built an advanced electronics industry within China, only to discover that its massive investments in technology upgrades had inadvertently given Beijing a power that could be weaponized. In Apple in China, journalist Patrick McGee draws on more than two hundred interviews with former executives and engineers, supplementing their stories with unreported meetings held by Steve Jobs, emails between top executives, and internal memos regarding threats from Chinese competition. The book highlights the unknown characters who were instrumental in Apple's ascent and who tried to forge a different path, including the Mormon missionary who established the Apple Store in China; the "Gang of Eight" executives tasked with placating Beijing; and an idealistic veteran whose hopes of improving the lives of factory workers were crushed by both Cupertino's operational demands and Xi Jinping's war on civil society. Apple in China is the sometimes disturbing and always revelatory story of how an outspoken, proud company that once praised "rebels" and "troublemakers"--the company that encouraged us all to "Think Different"--devolved into passively cooperating with a belligerent regime that increasingly controls its fate." --